(untitled) (Research, Society and Development, 2021)
Cover plants, due to their high biomass production capacity, and plants provide the soil with several benefits such as nutrient cycling, greater water retention and storage capacity, reduced temperature, increased aggregation and microbiota, physical protection against compaction. The objective of this work was to verify the growth of the fruit species of the cerrado, Dipteryx alata Vogel, as a consortium strategy with green fertilizers, Arachis pintoi Krapov. & W.C.Greg./Callopogonium mucunoides Desv., Crotalaria juncea L, Dolichos lablab L., [Urochloa decumbens (Stapf) R.D.Webster] with nitrogen and [Urochloa decumbens (Stapf) R.D.Webster] without nitrogen (control). The experiment covered the period from 2013 to 2017, in Rio Verde, Goiás, installed in a randomized block design, with five treatments (cover plants) and four replications. The evaluations included the macro and micronutrient contents in D. alata, biomass production by cover plants, soil moisture and biometric determinations of D. alata. The use of U. decumbens with nitrogen, D. lablab and C. juncea showed better performances in maintaining soil moisture, growth and early fruiting of D. alata, making it advantageous to use these types of consortium in its establishment under conditions of the Cerrado.